Differential Contribution of Monocytes to Heart Macrophages in Steady-State and After Myocardial Infarction - Timo Heidt; Gabriel Courties; Partha Dutta; Hendrik B. Sager; Matt Sebas; Yoshiko Iwamoto; Yuan Sun; Nicolas Da Silva; Peter Panizzi; Anja M. van der Laan; Filip K. Świrski; Ralph Weissleder; et al. (2014)
Rationale : Macrophages populate the steady-state myocardium. Previously, all macrophages were thought to arise from monocytes; however, it emerged that, in several organs, tissue-resident macrophages may self-maintain through local proliferation. Objective : Our aim was to study the contribution of monocytes to cardiac-resident macrophages in steady state, after macrophage depletion in CD11b DTR/+ mice and in myocardial infarction. Methods and Results : Using in vivo fate mapping and flow cytometry, we estimated that during steady state the heart macrophage population turns over in ≈1 month. To explore the source of cardiac-resident macrophages, we joined the circulation of mice using parabiosis. After 6 weeks, we observed blood monocyte chimerism of 35.3±3.4%, whereas heart macrophages showed a much lower chimerism of 2.7±0.5% ( P <0.01). Macrophages self-renewed locally through proliferation: 2.1±0.3% incorporated bromodeoxyuridine 2 hours after a single injection, and 13.7±1.4% heart macrophages stained positive for the cell cycle marker Ki-67. The cells likely participate in defense against infection, because we found them to ingest fluorescently labeled bacteria. In ischemic myocardium, we observed that tissue-resident macrophages died locally, whereas some also migrated to hematopoietic organs. If the steady state was perturbed by coronary ligation or diphtheria toxin–induced macrophage depletion in CD11b DTR/+ mice, blood monocytes replenished heart macrophages. However, in the chronic phase after myocardial infarction, macrophages residing in the infarct were again independent from the blood monocyte pool, returning to the steady-state situation. Conclusions : In this study, we show differential contribution of monocytes to heart macrophages during steady state, after macrophage depletion or in the acute and chronic phase after myocardial infarction. We found that macrophages participate in the immunosurveillance of myocardial tissue. These data correspond with previous studies on tissue-resident macrophages and raise important questions on the fate and function of macrophages during the development of heart failure.